PD-1/PD-L1 Based Combinational Cancer Therapy: Icing on the Cake - Zhang, Jian-ye; Yan, Yan-yan; Li, Jia-jun; Adhikari, Rameshwar; Fu, Li-wu (Frontiers in Pharmacology, 2020)
Cancer has been a major global health problem due to its high morbidity and mortality. While many chemotherapy agents have been studied and applied in preclinical and clinical trials, their use is limited due to its toxic side effects and poor tolerability. Monoclonal antibodies specific to the PD-1 and PD-L1 immune checkpoints have been approved for the treatment of various tumors. However, the application of PD-1/PD-L1 inhibitors remains suboptimal and thus another strategy of enhancing therapeutic efficacy involves the combination of checkpoint inhibitors and other agents. Various novel approaches are now in clinical trials. This review describes relevant investigations on combinatorial therapeutics using PD-1/PD-L1 inhibition.